2019
DOI: 10.1038/s41409-018-0410-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapy versus haploidentical transplantation in adults with acquired severe aplastic anemia

Abstract: Our study aimed to compare treatment outcomes between hematopoietic stem cell transplantation (HSCT) from haploidentical donors (HID) and immunosuppressive therapy (IST) in adults with acquired severe aplastic anemia (SAA). The medical records of 113 SAA adults who received IST, including rabbit ATG and cyclosporin (N = 37), or HID HSCT (N = 76) within 6 months of diagnosis at two institutions were retrospectively reviewed. Estimated 8-year overall survival (OS) was comparable between the IST and HID HSCT grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 36 publications
7
26
0
Order By: Relevance
“…5 Our previous study also showed a trend of higher FFS in patients older than 40 years of age in 8th year after HID-HSCT compared with those only received IST. 26 Based on these results, it is reasonable for selected patients to undergo HSCT to get complete hematopoietic recovery and favorable survival rate when facing the choice between HSCT and IST, with no need to be concerned about pros and cons of grafts from MSD, URD, or even HID.…”
Section: Discussionmentioning
confidence: 99%
“…5 Our previous study also showed a trend of higher FFS in patients older than 40 years of age in 8th year after HID-HSCT compared with those only received IST. 26 Based on these results, it is reasonable for selected patients to undergo HSCT to get complete hematopoietic recovery and favorable survival rate when facing the choice between HSCT and IST, with no need to be concerned about pros and cons of grafts from MSD, URD, or even HID.…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported the outcomes of AA patients treated with first-line allo-HSCT or IST [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The allo-HSCT group was divided into two subgroups: BMT-MRD and BMT-MUD.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…In a recent study, success was demonstrated in nonrefractory SAA with haploidentical HSCT without initial IST. 25 More data exist for haploidentical HSCT in the treatment of refractory SAA for patients without an MSD. 26,27 In 1 study, researchers demonstrated that 94% of patients achieved successful engraftment with a 3-year survival of 89%, 28 with similar findings in a registry-based comparison.…”
Section: Dr Hall Pediatric Hematologymentioning
confidence: 99%